Global Leadership Initiative on Malnutrition criteria for predicting surgical site infection in elective laparotomy patients - Octaviani, Pauline; Wulandari, Yohannessa; Ibrahim, Febiansyah; Andayani, Diyah Eka (Intelektual Pustaka Media Utama, 2024)
Laparotomy surgery patients are at risk for complication including surgical site infections (SSI) which are associated with high morbidity and mortality. Malnutrition has been identified as a risk factor for the occurrence of SSI but preoperative malnutrition identification remains low. The Global Leadership Initiative on Malnutrition (GLIM) has published a new, practical, and easily applicable definition of malnutrition. This study aims to evaluate whether malnutrition according to GLIM criteria is a predictor of SSI in elective laparotomy patients. This prospective cohort study involved 123 subjects aged 18-65 years undergoing elective laparotomy, without diabetes history. Their malnutrition status was assessed using GLIM criteria with bioelectrical impedance analysis (BIA) to evaluate muscle mass. A total 62 subjects were categorized into the malnutrition group and the remaining into nonmalnutrition group and then monitored for the presence of SSI up to 10 days postoperatively. SSI occurred in 13.8% of the subjects. The analysis showed a strong association between malnutrition and SSI in elective post laparotomy (RR 4.6; 95%CI 1.4-15.1; p=0.005). Malnutrition according to GLIM criteria is a significant predictor of SSI in elective post laparotomy patients.